Urban heat in tropicaL Kuala Lumpur: Microclimate, outdoor thermal comfort and mitigation by land-cover modification / Fong Chng Saun - Fong , Chng Saun (2020)
Urban heat island (UHI) is an urban warming phenomenon characterized by steep urban-rural temperature difference. Rapid land-use change in the urbanization process has introduced urban morphologies with impermeable surfaces and materials which causes higher heat retention in city centres. The emergence of urban hotspots is a growing concern due to the impact on the urban microclimate and human population. The comprehension of the multi-dimensional impact of UHI has become imperative to ensure good urban liveability especially in tropical cities where it is hot and humid annually. Hence, this study aims to explore the complex nexus of urban heat in terms of microclimate variations, human health implications and mitigation measures in Kuala Lumpur (KL), a rapidly developing tropical city. A study area with 500 m radius was chosen following standard microclimate monitoring procedure. Masjid Jamek (MJ), which is the selected study area from KL represents common urban morphology characterised with heterogeneous land cover and built types. This research is conducted in three phases in MJ. In Phase 1, continuous monitoring of the meteorological parameters is carried out at 2m height to identify urban microclimate variations near-surface level. In Phase 2, a cross-sectional approach is undertaken to identify the influence of urban heat on the outdoor thermal comfort (OTC) level and heat-related health implications. In Phase 3, a microclimate modelling and simulation approach is undertaken to explore urban heat mitigation measures in urban hotspots identified in the study area. Results from urban microclimate observation indicate the exposure of urban communities to distinctive hot and humid climate with high monthly air temperature (x̄=30.23°C, SD=3.90°C), monthly relative humidity (x̄=69.09%, SD=13.75%) and daily solar radiation (SR) (x̄=98.21 W/m2 , SD=119.74 W/m2 ). The hot-humid urban environment and predominant (43.3%) low wind activity of 0.5 to 1.5 m/s could be the reason for the thermal discomfort in the study area. Results from 1160 eligible respondents indicated more than half of the urban dwellers (n=633, 54.7%) reported thermal discomfort characterized with slight physiological heat stress (x̄=29.45°C PET, SD=2.11°C PET). Commonly reported heat-related health symptoms include heat exhaustion (n=569, 49.2%), tiredness (n=891, 77.0%), trouble relaxing (n=509, 44.0%) and being easily annoyed (n=471, 40.7%). Through Exploratory Factor Analysis, the 38 heat-related health symptoms are clustered into eight groups. Only pain (p=0.016), anxiety (p=0.022) and somatization (p=0.041) related symptoms were found to be significantly affected by UHI. Confounding factors such as gender, age group, ethnicity and duration of outdoor exposure in a day have varying influence towards the heat-related health outcomes. The Urban Microclimate Model developed through ENVI-MET for urban microclimate modelling and simulation was found to be reliable and accurate with moderate to strong (r=0.490 to 0.951) reproducibility of actual microclimate. Urban vegetation is the most effective urban heat mitigation strategy according to simulation results. A 15% increase in grass and tree coverage in the urban hotspot can result in a reduction of daily air temperature by 0.1°C and improvement in OTC level by 0.62°C PET. In conclusion, this study provided evidence of the deterioration of urban microclimate which led to a decline in OTC level and repercussions in heat-related health symptoms in a tropical city. The findings from the current study are expected to contribute to existing sustainable town planning practices in line with the vision of transforming KL into a top-tier liveable city.